The Store Is Dead - Long Live the Store - Bell, David; Gallino, Santiago; Moreno, Antoio; Yoder, James; Ueda, Daichi (MIT Sloan Management Review, 2018)
At a time when many traditional retailers are closing their physical stores, digitally native vertical brands such as Bonobos, which specializes in men's apparel, and Warby Parker, which specializes in eyeglasses, are aggressively expanding into offline locations. In this article, the authors explore two related trends: (1) the expansion of online-first retailers into offline stores that "supercharge" customer value and (2) the transformation of stores run by traditional, offline-first retailers from fulfillment-dominant centers into experience-dominant centers. As authors David R. Bell, Santiago Gallino, and Antonio Moreno note, as digitally native vertical brands have learned to build relationships with customers, traditional retailers have been reducing their store sizes and inventories and are attempting to improve and elevate the customer experience. "Showroom experiences," they write, "create better customers." When customers are exposed to the brand in a showroom, "they are better able to resolve any uncertainty about the nondigital attributes of the retailer's product." Similarly, the authors say, "showrooms create better retailers: When customers are physically present in the retail environment, observation of their behaviors can lead to meaningful insights." The authors developed their early insights into what customers value while working closely with Bonobos and Warby Parker. Through simulations, they saw that stores with smaller footprints and a higher level of service led to better results economically - improved margins, smoother logistics, and better control of inventory. They found that, rather than being dead, physical retail stores were very much alive with a profound shift in focus - from fulfillment to experience-oriented environments. The authors conclude that online-first retailers and traditional retailers have something to learn from each other. Offline-first retailers can benefit from copying the showroom concepts originated by online-first retailers; online-first retailers can benefit by opening more traditional stores.
Keywords: Electronic commerce; Web site development; Commerce électronique; Sites Web; Développement